Doppler Measurement of Differential Cross Sections in Crossed Beam Experiments: Dependence of the Detection Sensitivity With the Product Velocity. Issue 5 (1990) - Billy, N.; Girard, B.; Gouédard, G.; Vigué, J.
Abstract : Differential cross sections can be measured as a function of the internal state of a reaction product thanks to the analysis of the Doppler profile of the laser induced fluorescence detection line. This analysis is complicated by two effects: first, the LIF signal intensity depends on the interaction time of the molecule with the laser, and this time depends on the scattering angle, second, the angular and velocity distributions of the beams have non negligible widths. We present here a treatment of these effects in the case of theF + I 2 reaction for which we have measured the differential cross section by this technique. The same formalism is also applied to the deduction of the rovibrational distribution of the products from the relative intensities of the LIF lines.